Peters v. Kiff and the Debate About the Standing of White Defendants to Object to the Exclusion of Black Jurors After Batson: The Nonuse and Abuse of Precedent - Stanton D. Krauss (Washington University Law Quarterly, 1990)
In Batson v. Kentucky, the Supreme Court held that the racially based use of the prosecution's peremptory challenges to exclude blacks from a black defendant's jury violates the defendant's rights under the Equal Protection Clause of the fourteenth amendment. In addition, the Court noted that "denying a person participation in jury service on account of his race” in this manner violates the excluded juror's rights under that Clause. As might be expected, this decision has fueled the debate about whether white defendants may complain when the State uses peremptory challenges to exclude blacks from their juries. One remarkable aspect of this post-Batson controversy has been the way courts and commentators have treated Peters v. Kiff the only Supreme Court decision actually to determine the standing of a white defendant to protest discrimination against blacks in the selection of juries. More often than not, Peters has simply been ignored by courts considering this issue since Batson. Those exceptional opinions that do not overlook it entirely display a truly breathtaking inability accurately to report what the Justices said in that case. Nor has Peters fared much better at the hands of the commentators. There are two reasons why it is important to bring this situation to light. One is doctrinal: Peters must somehow be rescued from this morass, and its bearing upon the standing of white defendants to contest the use of peremptory challenges to exclude black jurors clarified. As a practical matter, this problem is pressing, because the Supreme Court will address the standing question this Term in Holland v. Illinois. The other reason to examine Peters’ fate, although not doctrinal in nature, is no less important: it is only by studying this spectacle that we can hope to learn what lessons it holds for our legal system and our profession. With these twin goals of exposure and explication in mind, I begin by introducing the reader to Batson and Peters. Once this has been accomplished, Part II of the Article surveys the treatment of Peters in the judicial opinions and commentary discussing the standing question. In Part III, I speculate about the reasons for the abuse that Peters has endured in this context.
Keywords: Peremptory challenges (Jury selection) -- Race; Batson v. Kentucky, 106 S. Ct. 1712